Dynamic active power sharing in a resistive microgrid - Augustine Egwebe (2016 4th International Symposium on Environmental Friendly Energies and Applications (EFEA), 2016)
This paper explores the use of a dynamic virtual impedance approach to load sharing as an alternative to the more generic droop load sharing scheme for low-voltage islanded micro-grids. The approach is based on taking advantage of the power decoupling capability of the virtual impedance scheme to facilitate appropriate load sharing based on the available generation capacity of distributed generation (DG) units. The proposed scheme identifies the DC operating zone of the photovoltaic inverter-based unit as irradiance levels change and conditions the virtual impedance loop for an efficient load sharing based on available generation. This dynamic approach allows taking into account the rating, output impedance and voltage limits of each unit. The proposed scheme provides energy saving; since energy demand from a local auxiliary generator is reduced. Results from the proposed dynamic scheme were tested on a P-f/Q-V droop, in the presence of virtual impedance, and results were compared with the conventional-static virtual impedance loading method. The proposed method is validated using MATLAB/SIMULINK simulations.